2007
DOI: 10.1007/s10484-007-9043-9
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Stress: The Effectiveness of Different Types of Music

Abstract: Listening to classical and self-selected relaxing music after exposure to a stressor should result in significant reductions in anxiety, anger, and sympathetic nervous system arousal, and increased relaxation compared to those who sit in silence or listen to heavy metal music. Fifty-six college students, 15 males and 41 females, were exposed to different types of music genres after experiencing a stressful test. Several 4 x 2 mixed design analyses of variance were conducted to determine the effects of music an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
195
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(242 citation statements)
references
References 7 publications
17
195
2
9
Order By: Relevance
“…Unaddressed, such fears can impact negatively on maternal depression rates (Britton, 2008) and similar findings present in the literature. Labbe et al, (2007), for example, found that listening to classical music was effective at reducing negative emotional states. Meanwhile, Bongard et al, (2008), found that the suppression of negative emotions led to increased physiological stress and increased the risk of cardiovascular disease.…”
Section: Relaxation and Stress Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unaddressed, such fears can impact negatively on maternal depression rates (Britton, 2008) and similar findings present in the literature. Labbe et al, (2007), for example, found that listening to classical music was effective at reducing negative emotional states. Meanwhile, Bongard et al, (2008), found that the suppression of negative emotions led to increased physiological stress and increased the risk of cardiovascular disease.…”
Section: Relaxation and Stress Reductionmentioning
confidence: 99%
“…Bernardi et al, (2009), for example, found that the body's autonomic functions such as heart rate were matched to the rhythms of music, resulting in increased heart rate when the music increased in volume and beat (p.3171). Music with a flowing soft melody, such as lullabies or classical music, is considered to be particularly relaxing and soothing (Kreutz et al, 2008;Labbe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta percepção de relaxamento é variável para cada indivíduo (Steelman, 1990;Labbé, et al, 2007;Trappe, 2011;Wakim et al, 2010;Beccaloni, 2011). Um estudo comparativo entre indivíduos que escutam músicas selecionadas individualmente, e indivíduos que ouviam música clássica, heavy metal ou que ficaram em silêncio por 20 minutos mostra diferença significativa no grau menor de ansiedade para aqueles que selecionavam as próprias músicas (Labbé et al, 2007). Outros autores descrevem que pacientes que escolhem ouvir suas músicas preferidas estão mais relaxados, confortáveis e confiantes além de menos ansiosos do que aqueles que não recebem intervenção alguma (Cooke et al, 2005;Bogopolsky, 2007).…”
Section: Música Como Agente Terapêutico Anti-estresseunclassified
“…A música pode alterar a resposta neurohormonal e imunológica em resposta ao estresse no trans operatório de cirurgias eletivas especialmente quando o tipo de música foi selecionado pelo próprio paciente (Hanser et al, 2005;Labbé et al, 2007;Leardi et al, 2007;Suda et al, 2008e Bradt et al, 2009. A música é considerada uma linguagem universal, mas o reflexo emocional e fisiológico que acompanha a música é extremamente individualizado.…”
Section: Música Como Agente Terapêutico Anti-estresseunclassified